Stunting prevention behaviors through the health action model in Maluku: a case study - Rumadaul, Dewi Syitra; Supriyati; Erlina, Erlin (BKM Public Health and Community Medicine, 2025)
Purpose: This study aims to explore stunting prevention behaviors in Sawai Village, Central Maluku District, using the health action model. Methods: A qualitative case study was conducted in April 2024, involving 25 participants purposively selected from various groups, including parents, caregivers, pregnant women, health workers, village officials, and cadres. Data were collected through interviews and observations, and analyzed using framework analysis supported by Opencode software. Results: Stunting prevention efforts in Sawai Village involve various stakeholders. The analysis identified nine key themes that shape stunting prevention behavior: 1) stunting prevention behaviors; 2) belief systems; 3) motivation systems; 4) normative systems; 5) knowledge; 6) skills; 7) physical environment; 8) socio-economic factors; and 9) socio-cultural factors. While community practices generally align with child health efforts, they are not explicitly aimed at stunting prevention. The involvement of fathers is minimal, cadres have limited technical capacity, and traditional beliefs, economic barriers, and lack of targeted knowledge hinder effective prevention. Conclusion: Although stunting prevention in Sawai Village involves multiple actors, it remains suboptimal. A comprehensive behavior change intervention based on the HAM framework is needed, along with Posyandu revitalization to enhance community participation and knowledge.